CRITICAL RACIAL LITERACY AWARENESS THROUGH AMERICAN LITERATURE: APPLYING THE SYNECTICS MODEL - Titis Dewi Cakrawati; Antonius Setyawan Sugeng Nur Agung; Henry Elisa (Journal of English Educational Study (JEES), 2023)
This study is aimed at describing the literature learning process through a Synectics Gordon teaching model in a class of Literary Appreciation. It is projected to promote literacy through implied and embedded values, particularly in regard to critical racial literacy through Asian American literature. This case study involves a lecturer and students in a Literary Appreciation course in an English department. The data were collected through observations and interviews. The implemented stages of the Synectics teaching model are: Describing the topic, Describing personal analogies, Identifying compressed conflicts, and Re-examining the original topic. Due to the time constraint, only one stage—Creating a new direct analogy—was elicited. The results suggest that the reading strategies i.e., shared reading aloud and visualization, enhanced students’ understanding of the story and elicit powerful emotions about the literary work. The findings of the study also imply that Gordon's Synectics model aids in raising students' awareness of racism and other associated social issues by allowing them to put themselves in the shoes of persons from various racial origins. Implementing the same method, this study recommends adapting local/ national literature in varied classrooms.